Avaliação do potencial genotóxico e mutagênico do efluente de uma refinaria de petróleo e dos rios sob sua influência, por meio de bioensaios com Oreochromis niloticus (Perciformes, Cichlidae) - Araújo, Cristiane Sueli Talhiaferro de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The petrochemical industry represents a sector of intense activity, in constant expansion and great economic importance for Brazil. In order to be used in various human activities petroleum needs to suffer a refinement process that, besides requiring large amounts of water, produces large amounts of wastes, which are discharged in hydric resources. Petroleum is a complex mixture mainly comprised by hydrocarbons, many of them are recognized as toxic chemicals, which are able to induce a considerable environmental pollution. Since water is an important resource for the maintenance of ecosystems and is also the final receiver of effluent discharges of the petroleum industry, there is an imminent need to monitor, constantly, the hydric resources that are influenced by this industrial activity, so that it can be ensured the environmental health. This study aimed, mainly, to analyze the quality of water samples derived from refinement process performed of the largest petroleum refinery in Brazil (REPLAN), in distinct steps of the industry treatment, and waters of rivers associated to its activity. Micronuclei and Nuclear Abnormalities tests were performed in erythrocytes of the fish species Oreochromis niloticus exposed to water samples derived from refinery use and to rivers under the influence of their effluents, in order to evaluate its possible toxic, genotoxic and mutagenic effects. The results obtained show that the treatment carried out by the refinery, during the evaluated periods, was effective, since the substances present in the water samples did not induce significant genotoxic and/or mutagenic alterations in the genetic material of the test organisms. On the other hand, when the substances present in the refinery effluent mix with the ones derived from other industrial activities developed upstream of this industry, the resultant compound, in some periods, presented genotoxic potencial, characterized by a rise of erythrocytic...

A indústria petroquímica representa um setor de intensa atividade e grande importância no Brasil, que continua em plena expansão. Para sua utilização, o petróleo precisa sofrer um processo de refino que demanda a utilização de grandes quantidades de água gerando também grande quantidade de efluentes lançados nos rios. O petróleo é uma mistura complexa composta principalmente por hidrocarbonetos, muitos deles reconhecidamente tóxicos e, portanto, seu processamento pode promover a contaminação do meio ambiente. Sendo a água o receptor final da descarga dessa indústria e um recurso tão importante para o abrigo e manutenção dos ecossistemas é de vital importância que se realizem atividades de biomonitoramento para garantir e proteger a qualidade dos recursos hídricos que sofrem influência desse tipo de atividade industrial garantindo assim a saúde ambiental. Este trabalho teve como objetivo principal analisar a qualidade das águas provenientes do processo de refino de petróleo de uma das maiores refinarias de petróleo do Brasil (REPLAN) durante as etapas do tratamento das águas residuais da indústria e das águas de rios associados a essa refinaria. Com o intuito de observar os possíveis efeitos tóxicos, genotóxicos e mutagênicos das diferentes amostras de água, peixes da espécie Oreochromis niloticus foram avaliados por meio dos testes do micronúcleo e de anormalidades nucleares em eritrócitos circulantes periféricos deste organismo. Os resultados obtidos indicaram que o tratamento realizado pela refinaria, nos períodos avaliados, foi eficiente uma vez que as substâncias presentes nas águas analisadas não foram capazes de promover alterações no material genético dos eritrócitos do organismo teste de maneira significativa. Desta forma, os resultados mostraram que as águas não possuem atividade genotóxica e/ou mutagênica. Por outro lado, quando as substâncias presentes nas águas da descarga pela...
Keywords: Genética; Toxicologia genética; Mutagenese; Petróleo - Refinarias - Subprodutos; Tilápia-do-Nilo; Monitoramento biológico; Ecossistemas aquáticos